2023
DOI: 10.1186/s12979-022-00326-4
|View full text |Cite
|
Sign up to set email alerts
|

Telomere and mitochondria mediated the association between dietary inflammatory index and mild cognitive impairment: A prospective cohort study

Abstract: Background Diet and chronic inflammation might play a major role in the pathogenesis of mild cognitive impairment (MCI). In addition, peripheral blood leukocyte telomere length (LTL) and mitochondrial DNA copy number (mtDNAcn) might mediate the relationship between inflammation and MCI risk. The purpose of the present study is to evaluate whether inflammatory potential of diet assessed by dietary inflammatory index (DII), chronic inflammation, peripheral blood LTL, and mtDNAcn were associated w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 38 publications
1
4
0
Order By: Relevance
“…found that the elderly people with higher levels of SIRI may be at a greater risk of developing cognitive impairment. Similarly, another study on mild cognitive impairment in older adults found the same result (Liu et al, 2023). Based on the results of the above study, the present study also found that higher SIRI levels were independently associated with early-onset PSCI.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…found that the elderly people with higher levels of SIRI may be at a greater risk of developing cognitive impairment. Similarly, another study on mild cognitive impairment in older adults found the same result (Liu et al, 2023). Based on the results of the above study, the present study also found that higher SIRI levels were independently associated with early-onset PSCI.…”
Section: Discussionsupporting
confidence: 87%
“…cognitive impairment over the past few years (Liu et al, 2023;. found that the elderly people with higher levels of SIRI may be at a greater risk of developing cognitive impairment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These ndings are in agreement with previous studies. [31][32][33] A pro-in ammatory diet can lead to increased levels of circulating in ammatory cytokines such as IL-1β, IL-6, TNF-α, and CRP, [20] which are associated not only with the metabolic disorders it causes (hyperinsulinemia, insulin resistance, dyslipidemia, hyperglycemia, and hypertension), but also with the resulting dysbiosis of the intestinal ecology, increased intestinal permeability, intestinal barrier dysfunction, and leakage of toxic bacterial metabolites into the circulatory system. [8] [34] This induction and ampli cation of systemic in ammation by a pro-in ammatory diet is considered to be related to cognitive impairment.…”
Section: Discussionmentioning
confidence: 99%
“…The study found that longer LTL was associated with better cognitive performance and lower risk of developing AD, vascular dementia, and their associated brain markers, pointing to TL as a strong indicator of AD development or cognitive impairment. Scarabino et al found that LTL was significantly longer in people with normal cognitive function than in people with mild cognitive impairment (MCI) [23] . In the elderly, the longer the LTL, the lower the risk of MCI [24][25][26] .…”
Section: Introductionmentioning
confidence: 99%